2022
DOI: 10.3390/molecules27175398
|View full text |Cite
|
Sign up to set email alerts
|

Bridging a Century-Old Problem: The Pathophysiology and Molecular Mechanisms of HA Filler-Induced Vascular Occlusion (FIVO)—Implications for Therapeutic Interventions

Abstract: Biocompatible hyaluronic acid (HA, hyaluronan) gel implants have altered the therapeutic landscape of surgery and medicine, fostering an array of innovative products that include viscosurgical aids, synovial supplements, and drug-eluting nanomaterials. However, it is perhaps the explosive growth in the cosmetic applications of injectable dermal fillers that has captured the brightest spotlight, emerging as the dominant modality in plastic surgery and aesthetic medicine. The popularity surge with which injectab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 243 publications
0
20
0
Order By: Relevance
“…1 Several studies confirmed that fractional ablative CO 2 laser and microneedling create channels to the dermis, which are wide enough to deliver black tissue marking ink and indocyanine green (size 300-900 nm). 3,13,14 However, dermal fillers such as hydrated PLLA (40-63 mm), 15 hyaluronic acid (Restylane products range 50-1,200 mm), 16 and calcium hydroxylapatite (25-45 mm) 17 are significantly larger.…”
Section: Discussionmentioning
confidence: 99%
“…1 Several studies confirmed that fractional ablative CO 2 laser and microneedling create channels to the dermis, which are wide enough to deliver black tissue marking ink and indocyanine green (size 300-900 nm). 3,13,14 However, dermal fillers such as hydrated PLLA (40-63 mm), 15 hyaluronic acid (Restylane products range 50-1,200 mm), 16 and calcium hydroxylapatite (25-45 mm) 17 are significantly larger.…”
Section: Discussionmentioning
confidence: 99%
“…42 Extracting blood to observe if its potential reflux may be effective to determine whether the blood vessels are impaired or not; however, the damage could be so minor that the technicians may not be able to observe the slight hemorrhage, while HA may still be able to penetrate into the blood vessels due to its hydrophilicity, and eventually to aggregate into large emboli. 43 With fillers injected in the neck and face having the potential to elicit serious, sometimes fatal complications, the technician must have a comprehensive understanding of the vascular distribution and variation, discuss potential complications with the patient in advance, and pay close attention to the patient's reaction during the operation. 40 Compared with previous studies, this study included more cases, explored the differences in facial embolism caused by different filler compositions and different filling sites, recorded the time of adverse reactions and the start of treatment, and described the prognosis of these cases.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to unmatched biocompatibility and bioactivity, the advent of HA hydrogels has heralded a new era in the field of aesthetic medicine [ 14 ]. However, with the increasing use of HA fillers comes along a drastic rise in the incidence of soft tissue filler adverse events (e.g., unacceptable cosmetic outcomes, blindness, allergies, hypersensitivity, and vascular-occlusive injuries) [ 15 , 16 , 17 ]. To overcome these burdensome complications, appropriate injections of exogenous HAase are performed by practitioners to degrade the injected filler.…”
Section: Introductionmentioning
confidence: 99%